'All these things don't take the pain away but they do help you to accept it': making the case for compassion-focused therapy in the management of persistent pain. Issue 1 (February 2020) - Gooding, Hannah; Stedmon, Jacqui; Crix, Doug
Background: People with persistent pain are frequently offered a pain management programme (PMP) as part of their care plan. Cognitive behavioural therapy (CBT) principles often underpin PMPs and has a good evidence base; nevertheless, more recent systematic reviews have suggested that its effectiveness is limited. Compassion-focused therapy (CFT) is a form of 'third-wave CBT' that offers an alternative and complementary view of pain, encouraging the person to be alongside their experience of pain and respond to it using skills of compassion they have learnt. Method: The current research explored the effectiveness of a 12-week CFT group for people who experience persistent pain. Research interviews explored CFT members' experiences of the CFT group. Feedback was collected on the facilitators' experience of running the group and questionnaire data collected on participants' mood, pain disability, acceptance of chronic pain and levels of self-criticism and self-reassurance. Results: Interviews were analysed using interpretative phenomenological analysis that revealed five master superordinate themes representative across all interviews. These were then triangulated with data from the questionnaires and facilitator feedback. Conclusion: In people whose persistent pain was compounded by a significant psychological component, a CFT group approach helped reduce feelings of isolation, improve ability to self-reassure, learn new ways of coping and develop a growing acceptance of the limitations associated with their pain. The possible implications for future clinical practice are considered.